2013
DOI: 10.2147/rrfms.s49768
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy case of suicide with three knives: a forensic and anatomical discussion

Abstract: We present a case of a 30-year-old man who committed suicide, using three knives, after a domestic disturbance in which he repeatedly stabbed his wife. During the inspection of the corpse of the man at the scene, two knives were found embedded in the neck and one in the abdomen. During the autopsy, we found two stab-incised injuries on the anterior surface of the neck in the lower section of the second segment bilaterally, one injury on the left side of the chest, and eleven injuries in the abdomen of the dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Our study was in agreement with the studies of Patel Ankur P et al 4 as they mention in their study that suicidal hanging (neck injury) were most common (97.5%) followed by accidental and homicidal. Our study was also consistent with the studies of Ajay Kumar S et al 3 , Shetty BS et al, 19 Aleksandra Apostolov et al, 20 Sikary AK et al, 21 Smith Srisont. 22 Our findings were in contrast with the studies of Zahid Hussein et al 7 as they have noticed homicidal deaths constituted maximum numbers (77.7%) of all autopsies conducted in their study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study was in agreement with the studies of Patel Ankur P et al 4 as they mention in their study that suicidal hanging (neck injury) were most common (97.5%) followed by accidental and homicidal. Our study was also consistent with the studies of Ajay Kumar S et al 3 , Shetty BS et al, 19 Aleksandra Apostolov et al, 20 Sikary AK et al, 21 Smith Srisont. 22 Our findings were in contrast with the studies of Zahid Hussein et al 7 as they have noticed homicidal deaths constituted maximum numbers (77.7%) of all autopsies conducted in their study.…”
Section: Resultssupporting
confidence: 92%
“…Our results of asphyxia deaths were in agreement with study done by Sharma BR et al 5 who found hanging (69%) outnumbered other asphyxial deaths like ligature and Manual strangulation. In our study, hemorrhagic shock was also one of the leading causes of death, which is similar to study of other authors like Zahid Hussain et al, 7 Shetty BS et al, 19 Parthasarathi Pramanik et al 23 , Smith Srisont et al 22, Aleksandar Apostolov et al 20 . In our study, minimum number of cause of death was due to decapitation i.e.…”
Section: Resultssupporting
confidence: 91%